Clichés tremblés dans deux poèmes de Louis MacNeice et Paul Muldoon - Florence Schneider (Revue LISA)
Romanticism and 19th century mass-production techniques shed a new light on originality and clichés, ready-made ideas and objects. Literary clichés and stereotypes imply repetitions, banality and are homonymous (in French) with photographic “clichés”, snapshots, which developed together with the rise of printed books and photographs. However, even if fixity is at the basis of both literary clichés and photographic snapshots, some poets propose to rehabilitate stereotypes, turning them into the roots of a blurred, slightly offset new vision. This is the case in the two poems under study here – “Homage to Clichés” written by Louis MacNeice in 1935 and “The Old Country,” a central poem in Horse Latitudes, a book written by Paul Muldoon in 2006.